Digital nomad’s sustainable responsibility: Exploring the effects of business and personal dimensions - Mourato, Inês Bravo (2022)
Digital nomads live outside of the classical organizational borders and can be seen as ‘contemporary entrepreneurs’ who bring disruptive business models into different industries, giving value to different working cultures and different types of capital. Because they are operating out of their home country, their social responsibility as entrepreneurs may have different implications. This study aims to explore, the outcomes of digital nomads’ social responsibility in terms of self-efficacy and innovation. To test the hypothesis model, a structural equation modelling (SEM) was used to analyze survey data. The results show that tourism firms should have always in mind their social responsibility levels, to attract this target niche and should pay attention to the fact that they are mostly solo travellers, so they value a lot the sense of community of a place and its legal, bureaucratic, and flexible terms of living. Results complement existing research by helping tourism businesses and destination managers to understand the implications of the digital nomads’ social responsibility.